A review of instrument techniques to measure magnetospheric cold electrons and ions - Maldonado, Carlos A.; Resendiz Lira, Pedro A.; Delzanno, Gian L.; Larsen, Brian A.; Reisenfeld, Daniel B.; Coffey, Victoria (Frontiers in Astronomy and Space Sciences, 2023)
A review of the instruments and techniques to directly measure the full distributions of the cold-ion and cold-electron populations in the magnetosphere is presented. Relatively few studies have focused on the cold plasma populations of the magnetosphere due to difficulties associated with obtaining measurements. The cold particle populations are defined here as those with total energy approximately <100 eV which is an energy range for which measurements are difficult (regardless of species), but which often make up the bulk of the plasma density. These populations have known and suspected impacts on the structure and dynamics of the magnetosphere but to date have not yet been measured adequately. The lack of accurate measurements cold ion and electron populations through the magnetosphere makes closure of these science questions extremely difficult if not impossible. Reaching closure will require innovations in plasma spectrometers and associated techniques required to obtain high-fidelity measurements of the cold ion and electron populations in the magnetosphere. This paper seeks to review the instruments and techniques that have been used to date and present possible options for future missions.